Economics of seismic safety for earthquake-prone Himalayan province of Uttarakhand in India. Issue 5 (11th November 2019) - Rautela, Piyoosh; Joshi, Girish Chandra; Ghildiyal, Shailesh
Abstract : Purpose: The purpose of this study is to estimate the cost of seismic resilience of identified vulnerable lifeline public buildings in earthquake-prone Himalayan province of Uttarakhand in India. Design/methodology/approach: Built area of the identified vulnerable lifeline buildings together with prevalent rate of construction has been considered for assessing the cost of seismic resilience while improvised rapid visual screening (RVS) technique, better suited to the built environment in the region, has been used for assessing seismic vulnerability. Findings: Investment of US250.08m is assessed as being required for ensuring seismic safety of 56.3, 62.1, 52.9, 64.6, 71.9 and 61.7% surveyed buildings, respectively, of fire and emergency services, police, health, education, local administration and other departments that are to become non-functional after an earthquake and result in a major socio-political turmoil. A total amount of US467.71m is estimated as being required for making all the buildings of these departments seismically resilient. Research limitations/implications: Actual investment estimates and reconstruction/retrofitting plans have to be prepared after detailed investigations as RVS technique only provides a preliminary estimate and helps in prioritising buildings for detailed investigations. Practical implications: This study is intended to provide a snapshot of the state of seismic vulnerability together with the financial resources required for corrective measures. This is to help the authorities in planning phased mobilisation of financial and technical resources for making the built environment seismically resilient. Social implications: This study is to bring forth awareness on this important issue and consequent public opinion in favour of safety of public facilities to ensure allocation of appropriate financial resources together with changes in techno-legal regime for the cause of earthquake safety. At the same time, this study is to motivate masses to voluntarily assess safety of their neighbourhood and undertake corrective measures. Originality/value: This study is based on primary data collected by the authors.